Могильники Ігрень (Огрінь) 8 та Олександрія доби енеоліту: проблеми датування та культурної приналежності - Рассамакін, Ю.Я. (Археологія, 2017)
Розглядаються дискусійні питання хронології та культурної приналежності двох ґрунтових могильників доби енеоліту — Ігрень 8 та Олександрія. The author discusses the issues of chronology of the known burial grounds. In this article, first of all, the location of a series of burials at Ihren 8 cemetery is revised and the earlier proposed point of view of the author himself is refined. An important moment for that was a revision of a paired bi-ritual burial 7-8 from the excavations in 1932 with the Trypillian painted cup of the second half of the Trypillia B/2. The author presents the arguments for the assumption that the two burials were made not at the same time. As a whole, singled out are the Early Chalcolithic burials with the peculiar for them position on a back with bended knees, accompanied by flint products, first of all tools made on long blades. The second later group is represented by two supine burials which date is determined by a Trypillian cup. Concerning Oleksandriia burial ground, the author confirms his earlier expressed position on the Early Chalcolithic age of the burials with long flint blades, presenting additional arguments, one of which is a publication of a new radiocarbon date for one of the burials. Based on the author’s terminology, graves of the both burial grounds are considered within the borders of the so called Skelianska culture existence, while in Ihren burial ground several burials could be made in the period of so called «hiatus» when there were the Stohivska group sites in the Dnipro River region. Автор рассматривает вопросы хронологии известных могильников. Прежде всего, в статье пересматривается расположение ряда погребений могильника Игрень 8 и уточняется точка зрения самого автора, предложенная им ранее. Важным моментом для этого послужил пересмотр парного биритуального погребения 7—8 из раскопок 1932 г., с трипольским расписным кубком второй половины Триполья В/2. Автор приводит аргументы о том, что речь идет о двух разновременных погребениях. В целом, выделяются погребения эпохи раннего энеолита с характерным для них положением на спине с согнутыми в коленях ногами, в сопровождении кремневых изделий, прежде всего, орудий, изготовленных на длинных пластинах. Вторая, более поздняя группа представлена двумя «вытянутыми» погребениями, время которых определяется по трипольскому кубку. Относительно могильника Александрия автор подтверждает свою ранее высказанную позицию о раннеэнеолитическом возрасте погребений с длинными кремневыми пластинами, приводя дополнительные аргументы, включая публикацию новой радиоуглеродной даты для одного из погребений. По терминологии автора, погребения обоих могильников рассматриваются в рамках существования так называемой скелянской культуры, а в могильнике Игрень некоторые погребения могли совершаться в период так называемого «хиатуса», когда в Поднепровье существовали памятники стоговской группы.